Biographical Sketch: Virgil Pendelton Gibney, MD, 1847–1927 - Brand, Richard A. (Springer-Verlag, 2009)
This biographical sketch on Virgil Pendelton Gibney corresponds to the historic text, The Classic: Chapter XVIII. Operative Treatment in Chronic Articular Ostitis, available at DOI 10.1007/s11999-009-1165-3.